Tradition Nabawiyyah Pedagogy: Shaping an Excellent Generation Through Education Based on QS. Al-Ahzab: 21 - Muhammad Raffin Althafullayya; Ali Akbar (Yayasan Adra Karima Hubbi, 2024)
Based on QS Al-Ahzab verse 21, this research elaborates on the crucial role of Sunnah Nabawiyyah-Based Education in shaping individual character and potential. The focus lies on education as the primary pillar of formation, with Sunnah Nabawiyyah Pedagogy as the guide derived from the teachings of the Prophet. The objective is to analyze the impact of applying Sunnah Nabawiyyah Pedagogy within the educational system, emphasizing the development of an excellent generation. The importance of integrating Islamic values into education is a primary highlight, and this research attempts to detail how these values can be incorporated into the curriculum and daily educational practices. The study identifies obstacles in implementing Sunnah Nabawiyyah Pedagogy and proposes concrete solutions. By exploring the positive impacts of implementing Sunnah Nabawiyyah Pedagogy, this research aims to provide valuable contributions on how to shape an excellent generation through education based on Islamic values. Furthermore, this research is expected to serve as a robust scientific foundation for better educational policy development, ensuring the application of pedagogy in accordance with religious guidance. A literature study method is used to delve into the concept of Sunnah Nabawiyyah Pedagogy, encompassing categories such as the analysis of Islamic education literature, quality education literature, curriculum literature analysis, and the literature on the implementation of Sunnah Pedagogy.